Optimasi Keamanan Jaringan Point to Point Menggunakan VPN IPSec dan GRE - Nana; Dadang Iskandar Mulyana (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Abstract At this time, where the development of technology and information is growing very fast. This has an impact on the security of data traffic on computer networks is very important, especially if it involves sensitive data. However, data security is still considered less important and attracts less attention from computer users. This is because it is still difficult to implement data security for both individual and corporate computer users. Virtual Private Network (VPN), is a network created to conduct encrypted data transactions between two or more authorized network users. VPN networks all use the internet so the security factor is very important. Some of the attacks that may occur on the internet network are Denial of Service (DoS) attacks, sniffing, spoofing, session hijacking, and many more. Researchers try to simulate network security using the GNS3 simulator to run two methods for point-to-point network security, namely by using IPSec VPN and GRE which functions to encrypt data traffic sent over public networks. At the time of uploading a file of 50 Megabytes from computer 2 and computer 3 to the FTP Server with a throughput of 0.878 Mbps with the IPSec method, the average ping is 75ms; and 1,060 Mbps throughput with the GRE method ping an average of 78ms; traffic is still normal, no problems on the network or request time out (RTO). Keywords— VPN, IPSec, GRE, Point to Point, GNS3.